A genetically encoded sensor for measuring serotonin dynamics - Wan, Jinxia; Peng, Wanling; Li, Xuelin; Qian, Tongrui; Song, Kun; Zeng, Jianzhi; Deng, Fei; Hao, Suyu; Feng, Jiesi; Zhang, Peng; Zhang, Yajun; Zou, Jing; et al. (Nature neuroscience, 2021)
Serotonin (5-HT) is a phylogenetically conserved monoamine neurotransmitter modulating important processes in the brain. To directly visualize the release of 5-HT, we developed a genetically encoded G-protein-coupled receptor (GPCR)-activation-based 5-HT (GRAB 5-HT ) sensor with high sensitivity, high selectivity, subsecond kinetics and subcellular resolution. GRAB 5-HT detects 5-HT release in multiple physiological and pathological conditions in both flies and mice and provides new insights into the dynamics and mechanisms of 5-HT signaling. The authors develop a genetically encoded GPCR-based sensor to image serotonin dynamics in behaving animals with high specificity, sensitivity and spatiotemporal resolution.